Case report: Multiple biventricular aneurysms in arrhythmogenic cardiomyopathy - Lin, Jiadong; Lu, Zhijuang; Lin, Mingqin; Wan, Ying; Li, Jianfeng; Huang, Xinsheng (Frontiers in Cardiovascular Medicine, 2023)
Arrhythmogenic cardiomyopathy (ACM) is a genetic disease characterized by fibro-fatty myocardial replacement and is clinically associated with malignant ventricular arrhythmias and sudden cardiac death. It presents a major diagnostic and therapeutic challenge due to its complex clinical presentation and multiparametric diagnostic scoring system that includes structural, histological, and electrocardiographic data. A 57-year-old man with a history of palpitation and premature ventricular contractions (PVC) experienced syncope and sustained ventricular tachycardia at a rate of 213 bpm, which was successfully rescued by synchronized cardioversion. Multiple ventricular aneurysms were found in the right ventricular free wall and the left ventricular apical regions, as well as mild biventricular systolic dysfunction, according to echocardiography and high-frequency ultrasound. The genetic analysis revealed the following desmoplakin genes, chr6-7585274-7585275, NM_004415, exon24, and c.7780delT (p.S2594Pfs*9), a heterozygous and likely pathogenic mutation, as the mutation sites in the patient and his 24-year-old daughter. During the 21-month follow-up, the patient did not experience syncope or pre-syncope symptoms while on β-blocker (bisoprolol) therapy. Among the multimodality imaging techniques of the ACM, late gadolinium enhancement on cardiac magnetic resonance (CMR) is accepted as a more objective indicator of myocardial fibrosis. Left ventricular systolic dysfunction, fibrosis on CMR, and frequent PVC are the primary and most sensitive clinical signs of desmoplakin cardiomyopathy. However, echocardiography continues to be the most commonly used imaging modality for assessing focal ventricular movement and structural abnormalities. The pathological characteristics of arrhythmogenic cardiomyopathy of the right ventricular anterior free wall and apical regions near the transducer can be better shown using high-frequency linear ultrasound with a higher resolution.